2018
DOI: 10.1007/s11596-018-1928-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lipoxin A4 Pretreatment on Cognitive Function of Aged Rats after Global Cerebral Ischemia Reperfusion

Abstract: The aim of the present study was to investigate the effect of lipoxin A4 (LXA4) pretreatment on cognitive function of aged rats after global cerebral ischemia reperfusion, and to explore its possible mechanism. Thirty-six aged male Sprague-Dawley rats were randomly divided into three groups (n=2 each): sham-operation group (S group), global cerebral ischemia reperfusion group (I/R group) and LXA4-pretreatment group (L group). The rat model of global cerebral ischemia reperfüsion was established by occlusion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In terms of poststroke cognitive impairment (PSCI), it was reported that, compared with patients without PSCI, the levels of LXA 4 were significantly reduced in PSCI patients, and the LXA 4 levels were positively correlated with the Mini-Mental State Examination scores (Wang et al, 2021). Inspiringly, LXA 4 pretreatment has been verified to improve cognitive function in aged rats after global cerebral ischemiareperfusion (Wu et al, 2018). Regarding poststroke depression, it was shown that the changes in the Beck Depression Inventory-II scores of patients after stroke were inversely correlated with LXA 4 level, hinting that LXA 4 may also be a protective factor for the prevention of depression after stroke (Kotlega et al, 2020).…”
Section: Ischemic Strokementioning
confidence: 99%
“…In terms of poststroke cognitive impairment (PSCI), it was reported that, compared with patients without PSCI, the levels of LXA 4 were significantly reduced in PSCI patients, and the LXA 4 levels were positively correlated with the Mini-Mental State Examination scores (Wang et al, 2021). Inspiringly, LXA 4 pretreatment has been verified to improve cognitive function in aged rats after global cerebral ischemiareperfusion (Wu et al, 2018). Regarding poststroke depression, it was shown that the changes in the Beck Depression Inventory-II scores of patients after stroke were inversely correlated with LXA 4 level, hinting that LXA 4 may also be a protective factor for the prevention of depression after stroke (Kotlega et al, 2020).…”
Section: Ischemic Strokementioning
confidence: 99%